Efek Reformasi Birokrasi Terhadap Kemajuan Ekonomi Daerah - A., Rustan; Kusumaningrum, Mayahayati (Pusjar SKPP Lembaga Administrasi Negara, 2016)
Local economic activity tends to be influenced by the capabilities of the bureaucracy. If the bureau cracyisable to implement good governance principles and it has high concern on public service to create citizen welfare, so that the trend of local economic activity tends to grow highly. Furthermore, if the bureaucracy can successively encourage local economic activity,the local development and public welfare may relatively increase. Therefore, the efforts to reform the local bureaucracy will drive local development through trickle-down effect. This study uses descriptivequantitative approach with linear regression analysis on cross-section data from 99 local governments in 2014 which are considered as pilot projects. The result is that the bureaucratic reform contributes apositive and statistically significant impact on local economy. Two of three components of the bureaucratic reform that are assessed, namely Accountability Performance of Local Government (AKIP) and Public Services, bring statistically-significant and positive impact to the localrevenue (PAD), and each point of PAD’s rise tends to createa statisticallysignificant and positive affect on local economic growth by 1.1%.Keywords: Bureaucratic Reform, Local Revenue, Regional Economic GrowthAktivitas ekonomi daerah cenderung dipengaruhi oleh kapabilitas birokrasi yang ada. Jika birokrasi menerapkan tata kelola pemerintahan yang baik dan pelayanan publiknya berorientasi pada kesejahteraan publik, maka kecenderungannya aktivitas ekonomi didaerah tersebut akan berkembang sangat tinggi. Jika birokrasi kemudian dapat mendorong aktivitas ekonomi daerah melaju, maka pembangunan dan kesejahteraan publik relatif akan meningkat. Oleh karenanya, upaya reformasi birokrasi diyakini akan membawa dampak turunan (trickle down effect) bagi kemajuan daerah. Penelitian ini secara deskriptif-kuantitatif menerapkan regresi linear pada data cross-section tahun 2014 pada 99 pemerintah daerah yang ditetapkan sebagai pilot project reformasi birokrasi. Hasil analisis menunjukkan bahwa reformasi birokrasi relatif berperan positif dan signifikan terhadap progres ekonomi daerah. Dari ketiga komponen reformasi birokrasi yang dinilai, dua diantaranya (variabel AKIP dan pelayanan publik) memberikan dampak secara statistik positif dan signifikan terhadap pertambahan nilai PAD, dan setiap peningkatan PAD tersebut secara statistik positifsignifikan mempengaruhi pertumbuhan ekonomi daerah sebesar 1,1%.Kata Kunci: Reformasi Birokrasi, Pendapatan Asli Daerah, Pertumbuhan Ekonomi Daerah